Use of genetic methods in wheat of breeding (Eurasian Journal of Ecology, 2016)
Increase wheat yields by improving its genotype - one of the most urgent problems of the rural economy. At present, using traditional methods of selection and genetic studies, such as backcross selection, distanthybridization, experimental mutagenesis, increased efficiency of obtaining genetically modified and improved forms of wheat. The high content of mono phosphorus (H3PO45%) leads to a weak mutagenic effect, and its 0.1%concentration promotes the development of plants biomass. Fertility rates of soft wheat hybrids with wild species (Т. timopheevii, Т. dicoccum and T. kiharae) depends on the direction of crossing and genotypes of varieties. Wild species as the parent component positively affect the high percentage of grain fertility. Genome of Nadezhda variety is compatible with genomes of wild species.
Keywords: Induced mutagenesis; isogenic; substituted lines of wheat; distant and intraspecific hybridization in soft bread wheat